2019
DOI: 10.1007/s10826-019-01607-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Parental Burnout among Finnish Parents: The Role of Socially Prescribed Perfectionism

Abstract: Objectives Although parental burnout can have detrimental consequences to families, the investigation of the syndrome is still in its infancy. The present study investigated what are the key family background variables that contribute to parental burnout among Finnish parents. Moreover, we investigated how self-oriented and socially prescribed perfectionism uniquely and interactively relate to parental burnout over and above the impacts of background variables. Methods Questionnaire-based data was collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
3
21

Year Published

2020
2020
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 42 publications
(107 reference statements)
11
108
3
21
Order By: Relevance
“…Thus, the PBA scores can be thought to represent real differences in parental burnout between different samples rather than measurement artefacts related to gender or level of education. In the present study, symptoms of parental burnout were more typical for mothers than fathers, whereas no mean level differences were found in the levels of parental burnout between highly educated and lower educated parents (see also, Sorkkila & Aunola, 2020). These results were in accordance with previous findings showing that the symptoms of parental burnout are to some extent dependent on parent’s gender but not on parental education (Mikolajczak, Raes et al ., 2018; Roskam et al ., 2018; Sorkkila & Aunola, 2020).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Thus, the PBA scores can be thought to represent real differences in parental burnout between different samples rather than measurement artefacts related to gender or level of education. In the present study, symptoms of parental burnout were more typical for mothers than fathers, whereas no mean level differences were found in the levels of parental burnout between highly educated and lower educated parents (see also, Sorkkila & Aunola, 2020). These results were in accordance with previous findings showing that the symptoms of parental burnout are to some extent dependent on parent’s gender but not on parental education (Mikolajczak, Raes et al ., 2018; Roskam et al ., 2018; Sorkkila & Aunola, 2020).…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, symptoms of parental burnout were more typical for mothers than fathers, whereas no mean level differences were found in the levels of parental burnout between highly educated and lower educated parents (see also, Sorkkila & Aunola, 2020). These results were in accordance with previous findings showing that the symptoms of parental burnout are to some extent dependent on parent’s gender but not on parental education (Mikolajczak, Raes et al ., 2018; Roskam et al ., 2018; Sorkkila & Aunola, 2020). Higher burnout levels of mothers compared to those of fathers may reflect the fact that mothers are generally more involved in children’s care and upbringing than fathers are (Mikolajczak, Raes et al ., 2018) and, thus, more prone to prolonged stress related on parenting.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies suggest that the role of a parent is more salient for women (Kerpelman & Schvaneveldt, 1999;Williams & Kelly, 2005) and that women experience higher parenting stress than men (Simon, 1992;Hildingsson & Thomas, 2013). Recently, Roskam, Brianda, and Mikolajczak (2018) and Sorkkila and Aunola (2019) showed that mothers may also be more prone than fathers to parental burnout. In line with those results, it was decided to study the group of mothers in the present project.…”
Section: Participantsmentioning
confidence: 99%
“…Still, the notion of parental burnout has gained traction (e.g., Cheng et al, 2020;Sorkkila & Aunola, 2020) and increasingly widespread recognition (e.g., Griffith, 2020).…”
mentioning
confidence: 99%